Densely Populated Single Atom Catalysts. Issue 2 (20th November 2019) - Wu, Jiabin; Xiong, Liukang; Zhao, Bote; Liu, Meilin; Huang, Liang
Abstract: Developing highly efficient electrocatalysts with low cost is critical for the wide‐spread application of sustainable and renewable energy conversion technologies. Single‐atom catalysts (SACs) have attracted considerable attention owing to their high catalytic activity, selectivity, and stability. However, the high surface energy of the single atoms often results in an extremely low loading of metal atom catalysts with limited mass activity. In this context, densely populated SACs are more promising for practical applications due to their high active surface area and mass activity. Herein, the recent research progress of high loading (≥5 wt%) SACs for different electrocatalytic applications is summarized. An overview of various synthesis and characterization strategies of SACs is presented in this review. The influence of appropriate substrates on the preparation of high metal loading SACs is also discussed. In addition, this review provides valuable insights into the current challenges and future opportunities in the field of single‐atom catalysts. Abstract : Densely populated single‐atom catalysts (SACs) are more promising for practical applications due to their high active surface area and mass activity. Herein, the recent research progress of high loading (≥5 wt%) SACs for different electrocatalytic applications is summarized. An overview of various synthesis and characterization strategies of SACs is also presented in this review.